Greenspace and human health: An umbrella review - Bo-Yi Yang (Elsevier, 2021)
Multiple systematic reviews on greenspace and health outcomes exist, but the overall evidence base remains unclear. Therefore, we performed an umbrella review to collect and appraise all relevant systematic reviews of epidemiological studies on greenness exposure and health. We searched PubMed, Embase, and Web of Science from inception to June 28, 2021, and screened references of relevant articles. Systematic reviews with or without meta-analyses of epidemiological studies that examined the associations of greenness with any health outcome were included. Two independent investigators performed study selection and data extraction. We also evaluated the methodological quality of the included systematic reviews using the “Assessing the Methodological Quality of Systematic Reviews 2” checklist. A total of 40 systematic reviews and meta-analyses were included, of which most were cross-sectional studies conducted in high-income countries. Greenspace exposure was estimated with various objective and subjective parameters. Beneficial associations of greenspace with all-cause and stroke-specific mortality, CVD morbidity, cardiometabolic factors, mental health, low birth weight, physical activity, sleep quality, and urban crime were observed. No consistent associations between greenspace and other health outcomes (e.g., cancers) were observed. Most of the included systematic reviews and meta-analyses had one or more limitations in methodology. Our findings provide supportive evidence regarding the beneficial effects of greenspace exposure on some aspects of human health. However, the credibility of such evidence was compromised by methodological limitations. Better performed systematic reviews and meta-analyses as well as longitudinal designed primary studies are needed to validate this conclusion. Public summary: • The evidence concerning greenspace and health outcomes remains unclear • We performed an umbrella review of 40 systematic reviews on greenspace and health • Greenspace exposure was estimated with various objective and subjective parameters • Greenspace was beneficially associated with several aspects of human health